2013
DOI: 10.1007/s11434-013-5844-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of grassland fence on the behavior and habitat area of the critically endangered Przewalski’s gazelle around the Qinghai Lake

Abstract: The trend of fencing grassland as livestock paddocks is spreading on the Eurasian steppe, however, its impacts on grassland wildlife are little known. In order to explore such impacts, we carried out a field study on how grassland fencing impacts Przewalski's gazelle (Procapra przewalskii), a species listed as EN (Endangered) by SSC/IUCN, on the Qinghai-Tibet Plateau. The results revealed that (1) in the fenced areas, daily movement distance of Przewalski's gazelle was 5081±1187 m (Hudong-Ketu) and 4110±912 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The population decline and range reduction seen in Przewalski's gazelle have both been strongly influenced by human activities (Li et al, 1999(Li et al, , 2012You et al, 2013). This gazelle was once on the brink of extinction (Jiang et al, 2000) and now only a few remnant subpopulations remain (Li et al, 2012).…”
Section: Extinction Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…The population decline and range reduction seen in Przewalski's gazelle have both been strongly influenced by human activities (Li et al, 1999(Li et al, , 2012You et al, 2013). This gazelle was once on the brink of extinction (Jiang et al, 2000) and now only a few remnant subpopulations remain (Li et al, 2012).…”
Section: Extinction Riskmentioning
confidence: 99%
“…The intensity of these threats varies across subpopulations (Li et al, 2012) but is high in most subpopulations examined in this study. You et al (2013) reported negative impacts of grassland fencing on Przewalski's gazelle, such as decreasing the size of their habitat and increasing mortality rate. Although some conservation facilities, including fenced passages between habitat areas and artificial watering pools were established in 2008, these are not yet being effectively used by the gazelles (Li et al, 2012).…”
Section: Extinction Riskmentioning
confidence: 99%
See 3 more Smart Citations